PENGEMBANGAN EKOWISATA PANTAI SEBAGAI DIVERSIFIKASI MATA PENCAHARIAN - Bambang Supriadi (Jurnal Pariwisata Pesona, 2016)
The quality of human resources are now in the poor level. By the diversification of people livelihoods (especially in ecotourism), it is possible to minimize the pressure on human resources. The purposes of this study are: 1. To analyze the social condition, economic and cultural community in the coastal resorts of South Malang Regency, 2. To describe a potential beach that has a chance to grow (development), 3. To describe the weakness and resistance of Tourist attraction management (planning and utilization), 4. To describe the opportunities of job opportunities in the sector of tourism services that will be utilized by the community around the tourist attraction area. Research methodology which was used in this study was Partisipatory Rural Appraisal approach (PRA), FGD (Focused Group Discussion), and SWOT. The target to be achieved in this study are: Knowing the strengths and weaknesses of Goa China beach when it is managed properly and professionally, Knowing the types of new tourism business opportunities which will be utilized for improvished families as employment opportunities (Guide, souvenirs seller, food and beverage sellers, etc.), and as policy recommendations on the development of coastal tourism to the government. The final conclusion is that the Tourist Attraction of Goa China has a negative value (-0.45) for the internal environment and a negative value (-0.35) for the external environment. Thus can be deduced that the position Goa China on Third Quadrant (difensif position). And it requires physical development, clean environment, and more public facilities, alternative businesses which needs to grow is mangrove cultivation and turtles breeding, and providing home stay, Internet network, and provision of unique souvenirs.